Learning, Prices, and Firm Dynamics - Bastos, Paulo; Dias, Daniel A.; Timoshenko, Olga A. (World Bank, Washington, DC, 2016)
This paper documents new facts about the joint evolution of firm performance and prices in international markets and proposes a theory of firm dynamics emphasizing the interaction between learning about demand and quality choice to explain the observed patterns. Using data from the Portuguese manufacturing sector, the paper documents that: (1) within narrow product categories, firms with longer spells of activity in export destinations tend to ship larger quantities at similar prices, thus obtaining larger export revenue; (2) older exporters tend to import more expensive inputs; and (3) revenue growth within destinations (conditional on initial size) tends to decline with market experience. The authors develop a model of endogenous input and output quality choices in a learning environment that is able to quantitatively account for these patterns. Counterfactual simulations reveal that minimum quality standards on exports reduce welfare by lowering entry in export markets and reallocating resources from old and large toward young and small firms.